Implementation of Smart Chatbot on Skincare E-Commerce Website Using Groq API - Lusi, Lusi; Tholib (NEWTON: Networking and Information Technology, 2026)
Slow and limited availability of customer service during specific hours continues to be a significant challenge in the e-commerce sector, especially when it comes to providing prompt, detailed, and accurate product information. This study effectively created and implemented an intelligent chatbot utilizing the Groq API, which is capable of delivering automated, real-time customer assistance around the clock. The Groq API was chosen for its capacity to handle natural language data with exceptionally low latency, facilitating quick interactions between users and the system. The chatbot system was integrated into a skincare e-commerce platform and developed using the Waterfall methodology, which outlines the stages of requirements analysis, system design, implementation, testing, and maintenance. The system underwent functional testing and showed rapid and precise response performance. The testing outcomes reveal that the chatbot can provide replies with an average response time of roughly ±1.4 seconds and a response accuracy rate of 90%. Moreover, the chatbot is adept at maintaining appropriate domain boundaries while addressing out-of-context or non-skincare-related inquiries. Based on these findings, it can be concluded that the designed chatbot operates effectively, improving customer service efficiency, speeding up the product consultation process, and potentially enhancing customer satisfaction and loyalty on skincare e-commerce sites.